Evaluation of confirmatory data following the Article 12 MRL review for sodium 5‐nitroguaiacolate, sodium o‐nitrophenolate and sodium p‐nitrophenolate (sodium nitrocompounds). (31st March 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: The applicant Asahi Chemical Europe s.r.o. submitted a request to the competent national authority in the Netherlands to evaluate the confirmatory data that were identified for the pesticide active substances sodium 5‐nitroguaiacolate, sodium o ‐nitrophenolate and sodium p ‐nitrophenolate (sodium nitrocompounds) in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gap related to validated analytical enforcement method, the validation data of a method for the determination of sodium nitrocompounds in high acid content commodities, dry commodities and hops (dried) was submitted. The data gap was considered satisfactorily addressed. The risk assessment performed for the three active substances sodium 5‐nitroguaiacolate, sodium o ‐nitrophenolate and sodium p ‐nitrophenolate in the framework of the MRL review remains valid.